Contesting globalization in the rise of nationalism: the case of us-china trade conflict - Trần, Công Hoàn (2020)
The study then concludes that globalization is changing, not ending. The previous approaches to globalization and nationalism need to be reviewed in several ways. The trade war itself has not ended, so the research around it still remains huge to be done to broaden understandings of international relations. This experience to globalization and nationalism can partly contribute to the debate of the dominating movement is either globalization or nationalism